Population responses of Chinook salmon to two decades of restoration of estuary nursery habitat - Greene, Correigh M.; Beamer, Eric M.; Munsch, Stuart H.; Chamberlin, Joshua W.; LeMoine, Michael T.; Anderson, Joseph H. (Frontiers in Marine Science, 2025)
Estuaries comprise important but often-degraded fish nursery habitat. People have invested considerable resources into restoring estuaries to rehabilitate habitats, but comparatively little work has evaluated population outcomes for target species. Here, we examined the response of a threatened population of Chinook salmon (Oncorhynchus tshawytscha) to estuary restoration in their natal tidal delta, and observed demographic changes consistent with increasing nursery habitat capacity and quality. We leveraged three decades of monitoring before, during, and after restoration in the Skagit River delta, and compared demographic patterns in restored and unrestored forks within the delta, and in locations landward and seaward of the delta. We hypothesized that restoration in tidal deltas should result in reductions in local densities, and reduced density-dependent spillover of juveniles into nearshore waters. We also examined other predictions that were more ambiguous and depended upon biological mechanisms. We found that (1) delta restoration led to lower juvenile densities overall and greater juvenile densities when conspecific abundances were high, and (2) individual juveniles were smaller overall and their lengths declined less when densities were higher. We also monitored juvenile salmon in nearshore waters seaward of the delta. Following delta restoration, (3) juvenile catches in nearshore marine waters declined relative to delta habitat change, and (4) the prevalence of nearshore fry (<~45 mm) — a phase thought to benefit more from delta nursery habitats — decreased overall. These findings suggest that greater nursery habitat capacity in the delta allowed salmon to spread out and accommodated higher salmon numbers when juvenile outmigrations were especially high. They also suggest that restoration promoted the use of delta habitats by smaller fish while alleviating competitive effects on growth. Furthermore, they suggest that greater delta habitat capacity supported more juveniles, decreasing overflow to nearshore environments, especially for the smallest, most vulnerable salmon that presumably benefit most from growth before entering nearshore waters. Thus, estuary restoration appeared to alleviate density-dependent constraints on rearing and growth. These findings provide empirical support for restoring estuaries in human-stressed landscapes to rehabilitate nursery habitat functions for Chinook salmon and, potentially, other species and life stages.